2020
DOI: 10.1504/ijmp.2020.104069
|View full text |Cite
|
Sign up to set email alerts
|

A model for measuring the direct and indirect impact of organisational culture factors and knowledge-sharing on the success of employee performance (field study in Jordanian Islamic banks sector)

Abstract: The purpose of this paper was to analyse the direct and indirect impact of organisational culture factors, which are seen to consist of participation, compliance, consistency, adaptability, and strategic direction, with the objective to achieve success in employee performance through the mediation of knowledge-sharing. Additionally, the research is based on an empirical research encompassing a sample of three Islamic banks (totalling 235 employees) in Jordan where respondents answered the survey questions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…Organisational culture has a positive and significant impact on employees' performance ( (Dwivedi, 2001;Stare, 2012;Jarrah et al, 2020). However, this study is in contrast with the earlier findings.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Organisational culture has a positive and significant impact on employees' performance ( (Dwivedi, 2001;Stare, 2012;Jarrah et al, 2020). However, this study is in contrast with the earlier findings.…”
Section: Discussioncontrasting
confidence: 67%
“…Psychological capital perfectly mediates the relationship between spiritual leadership and employee performance (Baykal and Zehir, 2018). The available literature supports the positive cause and effect relationship between organisational culture & job performance (Jarrah et al, 2020;Galbreath, 2010) and organisational culture & employees' psychological capital (Manchala and Sudhakar, 2017;Luthans et al, 2007). There is also a positive cause and effect relationship between PsyCap and employees' job performance (Luthans et al, 2007).…”
Section: The Mediating Role Of Psychological Capitalmentioning
confidence: 81%
See 1 more Smart Citation
“…Organizational culture has positive implications for employee performance of 20.9%. Implementation of organizational culture is able to have a positive effect on employee behavior in accordance with organizational values (Ababneh, 2020;Alsheikh et al, 2017;Jarrah et al, 2020;Kala'Lembang et al, 2015). Indicators are able to manifest the relationship between organizational culture to employee performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the same direction, Memon et al [63] reported a relationship between an organizational culture that encourages its workers and the sharing of tacit knowledge. Jarrah et al [64] supported the hypothesis that knowledge sharing mediates the relationship between a culture based on obedience and organizational performance. Suppiah and Sandhu [65] found that organizational culture influenced tacit knowledge sharing.…”
Section: Knowledge Sharing and Culturementioning
confidence: 93%